Physicochemical Parameters in the Soil of Farin Gada Farm Jos North Local Government, Plateau - Abubakar, Musa Yahaya; Dwanga, Danladi Mudwa; Kingsley, Emmanuel Chinedu; Muhammad, Shittu Abubakar; Adam, Ansar Bilyamin (Kwaghe International Journal of Sciences and Technology, 2024)
Soil is a part of the earth that is made up of various mixtures, including organic matter, minerals, gases, liquids, and organisms that together support life. Because soil is used to cultivate foods for animals worldwide, it plays a critical role in the global cultivation of wheat, rice, mustard, vegetables, and fruits, among other crops. Nigerian agriculture uses this soil, and the physical and chemical conditions of the land make it necessary to implement other management practices properly. For this reason, the physicochemical study of soil is very significant because it considers both the physical and chemical properties that affect soil productivity. This study the parameters of soil in order to improve the agricultural activities. The result of study shows that the Physicochemical properties of the soil samples at Farin Gada reveals that temperature of soil were found to be 27oC, pH ranges from 6.38±0.09 to 7.47±0.50, conductivity ranges from 0.15±0.01 to 0.42±0.08, Moisture Contents ranges from 0.48±0.82 to13.17 ±0.8, Cation Exchange Capacity (CEC) ranges from0.53±0. to 0.54±0.86 and the organic matter ranges from 13.51±0.79 to 43.24±0.82, respectively.